2017
DOI: 10.1002/14651858.cd006396.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to prevent occupational noise-induced hearing loss

Abstract: There is very low-quality evidence that implementation of stricter legislation can reduce noise levels in workplaces. Controlled studies of other engineering control interventions in the field have not been conducted. There is moderate-quality evidence that training of proper insertion of earplugs significantly reduces noise exposure at short-term follow-up but long-term follow-up is still needed.There is very low-quality evidence that the better use of hearing protection devices as part of HLPPs reduces the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 95 publications
4
71
0
15
Order By: Relevance
“…NIHL is related to multiple factors. In addition to occupational noise, other factors (such as organic solvent [4], high-temperature [5], no use of hearing protection device [6], alcohol [7], genes [8], comorbidity [9], etc.) may be independent factors or have a synergistic effect with noise to increase the risk of NIHL.…”
Section: Introductionmentioning
confidence: 99%
“…NIHL is related to multiple factors. In addition to occupational noise, other factors (such as organic solvent [4], high-temperature [5], no use of hearing protection device [6], alcohol [7], genes [8], comorbidity [9], etc.) may be independent factors or have a synergistic effect with noise to increase the risk of NIHL.…”
Section: Introductionmentioning
confidence: 99%
“…There's a significant distance between the theory (the guidance given) and the practice (that which is done). Authors state that implementing a more rigid legislation in companies may reduce the levels of noise in the work stations 27 . Some health professionals, specifically those of occupational medicine, speechlanguage pathology and audiology, are acquainted with important elements of the HCP and believe to be developing the program.…”
Section: Discussionmentioning
confidence: 99%
“…When engineering and administrative measures are not feasible or do not reduce noise to safe levels, HPDs such as earplugs and ear muffs become necessary—as does sufficient training for proper use of HPDs. A meta‐analysis of HPD training programs demonstrated that noise attenuation was 8.5 dB better in workers using HPD that received training than those that did not . Within Mining and OGE, HPDs are usually the first worker protection employed.…”
Section: Discussionmentioning
confidence: 99%